Direct and indirect impacts of climate change on forests: three case studies from British Columbia - Daniels, Lori D; Maertens, Thomas B; Stan, Amanda B; McCloskey, Shane P. J; Cochrane, Jed D; Gray, Robert W (Canadian journal of plant pathology, 2011)
Climate is an important driver of forest dynamics. In this paper, we present three case studies from the forests of British Columbia to illustrate the direct and indirect effects of climatic variation and global warming on forest composition and function. (1) Tree mortality rates in old forests of western North America have doubled in recent decades. Regional warming and water deficits directly affected tree death rates or indirectly increased insect and pathogen activity and wind storms causing tree deaths. Concurrently, tree density and basal area declined significantly, indicating lagged growth responses of surviving trees or long-term decline of these forests. (2) Yellow-cedar decline along coastal British Columbia and Alaska shows that small changes in average climatic conditions, coupled with extreme weather events, can have large ecological effects. A small persistent increase in mean temperatures has reduced snow-cover depth and duration. Coupled with extreme cold events which damage unprotected tree roots, these climatic changes are considered the primary cause of widespread yellow-cedar mortality. (3) Interactions between climate and disturbance are complex in the mountain forests of the East Kootenay region. Understanding historic climate–fire interactions is key to anticipating future frequent and severe fires. Here, climate change effects may be exacerbated by the cumulative effects of human land use, fire exclusion and mountain pine beetle outbreaks. We conclude that understanding past climate variation and its effects on forests help us to anticipate the potential effects of global warming.